2011
DOI: 10.1182/blood-2011-02-338434
|View full text |Cite
|
Sign up to set email alerts
|

A shared gene expression signature in mouse models of EBV-associated and non–EBV-associated Burkitt lymphoma

Abstract: The link between EBV infection and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
(92 reference statements)
3
9
0
Order By: Relevance
“…LMP2A is also known to be expressed in the GC B cells of healthy virus carriers, in which cells it has been assumed, based on previous studies in transgenic mouse models and in lymphoblastoid cell lines, to provide a surrogate BCR signal . In the present study we have shown that LMP2A expression does indeed recapitulate many of the transcriptional changes induced by BCR ligation in primary human germinal centre B cells.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…LMP2A is also known to be expressed in the GC B cells of healthy virus carriers, in which cells it has been assumed, based on previous studies in transgenic mouse models and in lymphoblastoid cell lines, to provide a surrogate BCR signal . In the present study we have shown that LMP2A expression does indeed recapitulate many of the transcriptional changes induced by BCR ligation in primary human germinal centre B cells.…”
Section: Discussionsupporting
confidence: 68%
“…BZLF1 has also been shown to bind to the EGR1 promoter and activate its expression . Recently, Egr‐1 was reported to be up‐regulated in an LMP2A‐expressing mouse model of Burkitt's lymphoma, suggesting that Egr‐1 might also be regulated by LMP2A .…”
Section: Introductionmentioning
confidence: 99%
“…Both lines express the transgene under the control of the IgH promoter and enhancer region, rendering transgene expression B cell-specific. The well-described LMP2A Tg6 line has no gross defect in B cell numbers, B cell development, or BCR expression [31] , [32] , [43] . In LMP1 lineage 3 mice, modest alterations have been described in B cell maturation in the periphery, as well as the ablation of germinal center (GC) formation in response to antigen [16] .…”
Section: Resultsmentioning
confidence: 99%
“…Two others (EPCAM epithelial cell specific trans-membrane glycoprotein, and PPARG chemokine), as well as REG4, are being explored for targeted cancer therapy [64-66]. The last of the seven, BBC3 (also called p53 up-regulated modulator of apoptosis, or PUMA) is reportedly upregulated by EBV LMP2A and reigned in by EBV miR-BART5 in cell line models [67,68], suggesting that this BCL2 family member is tightly regulated by the virus.…”
Section: Discussionmentioning
confidence: 99%